EFFECT OF RANDOM FIBER DISTRIBUTION ON LONGITUDINAL COMPRESSIVE BEHAVIOR OF COMPOSITE MATERIALS - ZHANG Li; XU Dong; ZHANG ShuFeng; JIANG YuanXiang (Jixie qiangdu)
Random fiber distribution may lead to randomness of longitudinal compressive behavior of fiber reinforced plastics（FRP）.To mimic random fiber distribution over the cross-section,a new algorithm named Latin Hypercube Sampling based on Random Sequential Expansion（LHS-RSE） is proposed,which can simulate the random fiber distribution of FRP with fiber volume ratio as high as 70%.Then,3 D FE model with random fiber distribution of unidirectional fiber reinforced plastic T300/914 is developed in Abaqus/Standard to investigate the influence of random fiber distribution on the compressive behavior.It is shown that random fiber distribution over cross section greatly compromises the longitudinal compressive strength of FRP.Random distribution of longitudinal compressive strength resulted by random fiber distribution tends to follow normal or lognormal distribution.